Bending of a Seven Layer Beam with Foam Cores - Krzysztof MAGNUCKI; Szymon MILECKI; Jerzy LEWIŃSKI; Piotr KĘDZIA (Engineering Transactions, 2018)
The subject of the paper is a seven layer beam with foam cores. The structure of the beam is symmetrical. The beam is composed of the main core, two inner sheets, two second cores and two outer sheets. The main core and two face cores are metal and polyurethane foams, while the sheets are metal. The analytical model of the beam is developed. The displacement and strain fields are formulated with consideration of the Zig-Zag hypothesis of deformation of a flat cross-section of the beam. The governing differential equations for the seven layer beam are obtained based on the stationary total potential energy. The detailed studies are devoted to deflections and stresses of the beams under a uniformly distributed load. The influence of the foam type of cores on the deflections and stresses of the beam is analysed. Moreover, the numerical FEM-model of the beam is developed. The analytical solution is compared to numerical calculations – FEM studies (ABAQUS System and SolidWorks Simulation). The results of the analysis are presented in Tables and Figures.